(untitled) (Journal of Business and Technology (Dhaka), 2012)
The Readymade garment (RMG) industry of Bangladesh has become the backbone of the national economy. It is the highest foreign exchange earner, it employs largest number of people and it generates vibration for other sectors. Despite the impressive performance, the RMG industry has several problems especially in its labor management practices. As a result, a lot of turmoil and disputes often rock the industry. The empirical evidence implies that labor law of the country has not been put into practice appropriately in the RMG industry. Proper and satisfactory implementation of labor law can eradicate the disputes and stop the commotions in the industry. In this study an attempt has been made to find out the relation between implementation of Bangladesh Labor Act 2006 and labor unrest. Seven major factors have been considered which are closely related to labor unrest. The study reveals that employees’ wages and payment is the most significantly correlated factor to labor unrest. DOI: http://dx.doi.org/10.3329/jbt.v5i2.9932 Journal of Business and Technology (Dhaka) Vol. 5(2), July-December, 2010 1-18